(untitled) (Indian Journal of Animal Production and Management, 2026)
The uropygial gland is an exocrine gland that produces a variety of biochemical and is located above the tail of birds, there has been little empirical research on its histological structure, this study was to investigate the histochemical and histoenzymic features of the uropygial gland in Sturnus Vulgaris. Five birds of European starling were obtained from local market in Basrah province, the tissue samples were stained by traditional and special stains Van Gieson, periodic acid-shiff (PAS) and demonstration of alkaline phosphatase (ALP). The histochemical analysis of gland was recorde in vangieson stain positive reaction was observed in the collagen fibers of capsule, with strong intensive to (PAS) in all layers of gland also the strong reaction of (ALP) was revealed in all layers of secretory tubules. The reason for this study was a paucity of knowledge on the histochemical and histoenzymic features of uropygial glands in starling birds via used the special stains.